Effect of Grafting Dates on Graft-take Success and Sapling Growth of Persian Walnut (Juglans regia L.) Under Open Field Condition of Jumla, Nepal - Chalise, Basant; Bhusal, Yubrai; Kalauni, Santosh; Giri, Raj Kumar; Luitel, Binod Prasad (Nepalese Horticulture, 2021)
A field experiment was carried out at Horticultural Research Station, Rajikot, Jumla to determine the best grafting date of walnut for the highest graft-take success and sapling growth. The experiment was conducted during the two consecutive years 2017, and 2018. Two varieties namely ‘Hartley’ and ‘Payne’ and four different dates of grafting viz. 15th March, 22nd March, 29th March, and 5th April were used as the treatment and the experiment was laid out in split-plot design. Each treatment was assigned with ten grafts with five replications per treatment. The measured parameters for the experiments included graft-take success (%), final scion diameter (cm), growth on scion diameter (%), number of primary branches per plant, plant spread (cm), and number of leaf per plant. The pooled value of observation for two years showed highly significant effect of variety and grafting date on grafting-take. ‘Hartley’ variety showed maximum graft-take success (73.2%) and ‘Payne’ with the least success (54.0%). The pooled value of two successive years showed the highest graft-take success (70.0%) on 15th of March, significantly at par with 22nd March (64.5%) and 29th March (67.0 %) grafting. Grafting on 15th March was also superior in terms of number of leaves (31.7), and least was observed for grafting on 29th March (20.5). In essence, variety ‘Hartley’ was found to record higher graft-take success with 15th March as the optimum grafting date under Jumla condition.